The Meiji restoration: Japan as a global nation - Hellyer, Robert I.; Fuess, Harald (Cambridge University Press, 2020)
In world history, the Meiji Restoration of 1868 ranks as a revolutionary watershed, on a par with the American and French Revolutions. In this volume, leading historians from North America, Europe, and Japan employ global history in novel ways to offer fresh economic, social, political, cultural, and military perspectives on the Meiji Restoration and the subsequent creation of the modern Japanese nation-state. Seamlessly mixing meta- and micro-history, the authors examine how the Japanese state and Japanese people engaged with global trends of the early nineteenth century. They also explore the internal military conflicts that marked the 1860s and the process of reconciliation after 1868. They conclude with discussions of how new political, cultural, and diplomatic institutions were created as Japan emerged as a global nation, defined in multiple ways by its place in the world.